Familial primary biliary cirrhosis and autoimmune cholangitis. - Agarwal, K; Jones, D; Watt, F; Burt, A; Floreani, A; Bassendine, M (2002)
AIM: Autoimmune cholangitis has been proposed as a separate disease entity from primary biliary cirrhosis without serum antimitochondrial antibodies. The ultimate answer to the question of whether autoimmune cholangitis and primary biliary cirrhosis are distinct will require detailed comparison of aetiologic factors and pathogenic mechanisms. METHODS AND RESULTS: Two families are described each of which has one member with classical antimitochondrial antibody positive biopsy-proven primary biliary cirrhosis and a first degree relative with antimitochondrial antibody negative but antinuclear antibody positive autoimmune cholangitis (biopsy proven in one case). Study of such families should allow analysis of the contribution of shared genetic risk factors versus varying environmental triggering mechanisms to disease pathogenesis. CONCLUSIONS: We suggest a European registry of families, such as the two described, which are rare within one centre, to facilitate elucidation of pathogenetic factors.